Non-fullerene acceptor engineering with three-dimensional thiophene/selenophene-annulated perylene diimides for high performance polymer solar cells. Issue 46 (8th November 2018) - Li, Gang; Wang, Shuaihua; Liu, Tao; Hao, Pin; Liu, Zhenhua; Li, Fengting; Yang, Lian-Ming; Zhang, Yu; Li, Dandan; Yang, Shufan; Zhao, Jianfeng; Li, Jiewei; et al.
Abstract : High efficiencies of 6.85% and 7.63% are obtained in non-fullerene OSCs usingTPE-PDI4 -S /TPE-PDI4 -Se as the acceptors andPBDB-T1 as the donor. Abstract : We report two new propeller-shaped perylene diimide (PDI ) acceptors based on tetraphenylethylene (TPE ) as the core and flanked with S/Se-fusedPDIs, named asTPE-PDI4 -S andTPE-PDI4 -Se . Compared to the sulfur-annulated counterpart, TPE-PDI4 -Se exhibits a blue-shifted absorption spectrum, stronger absorption in the region of 400–600 nm, higher LUMO energy level and twisted molecular geometry. TheTPE-PDI4 -Se based device withPBDB-T1 as the donor achieved a power conversion efficiency (PCE) of 7.63% along with a high V OC of 1.08 V, a J SC of 10.28 mA cm −2 and a high fill factor of 68.8%, a 11.4% boost in PCE with respect to theTPE-PDI4 -S based control device (6.85%). The high photovoltaic performance of theTPE-PDI4 -Se based device can be attributed to its relatively high-lying LUMO level, complementary absorption spectra with the donor material, relatively favorable morphology and balanced carrier transport. To the best of our knowledge, a PCE of 7.63% is among the highest values forTPE core-based non-fullerene organic solar cells. Overall, our work provides a simple and effective molecule-designing method to promote the PCE of non-fullerene OSCs.